Nano theranostics involved in bladder cancer treatment - Kunpeng Liu; Qixi Mo; Zhenshan Ding; Shicong Lai; Jian Ren; Qingsong Yu (Exploration of Drug Science)
Bladder cancer (BC) is a complex disease with multiple clinical manifestations and treatment challenges, and current standard-of-care therapies remain limited and unfavorable. Theranostics, the integration of diagnostic and therapeutic technologies, has emerged as a promising strategy to address these challenges. The rapid development of nanomedicine has been a source of hope for the improvement of BC therapies and diagnostics by reducing side effects, enhancing tumor suppression, and overcoming drug resistance. Metal nanoparticles (NPs), inorganic NPs, polymer NPs, etc. have their respective advantages and show encouraging potential in the therapy of BC. In this review, we provide an overview on the state of the art in nanotechnology-based theranostics for BC, offering insights into the design and discovery of novel NPs for future BC management.